ANÁLISIS E INTERPRETACIÓN A LOS ESTADOS FINANCIEROS Y PROPUESTAS DE MEJORA A LA COOPERATIVA DE AHORRO Y CRÉDITO HUAQUILLAS LTDA. DEL CANTÓN HUAQUILLAS, PROVINCIA DE EL ORO, PERÍODO 2016-2017 - MALLA DÍAZ, SHEIMY BRIGGITTE (2019)
The present thesis work entitled: "ANALYSIS AND INTERPRETATION TO THE FINANCIAL STATES AND PROPOSALS FOR IMPROVEMENT TO THE COOPERATIVE OF SAVING AND CREDIT HUAQUILLAS LTDA. DEL CANTÓN HUAQUILLAS, PROVINCIA DE EL ORO, PERÍODO 2016-2017", has the firm purpose of knowing the current economic-financial situation and thus contributing to an adequate decision making for the satisfactory development of the institution, so that they can mitigate certain risks, at the same time take advantage of financial resources and improve its profitability. For the preparation of the financial analysis, each one of the proposed objectives is taken into consideration, among which is the vertical and horizontal analysis of the 2016-2017 financial statements, with the purpose of knowing the financial structure and at the same time the different variations of assets, liabilities, equity, income and expenses; then the financial indicators of the PERLAS Monitoring System are applied, in order to know the capacity that the institution has at the moment of responding to the obligations with the public, that is to say the liquidity, solvency, profitability and level of indebtedness, and on the basis of this the respective improvement proposals can be made and in this way achieve a profitability that allows the cooperative to continue growing, through the efficiency and effectiveness in the decision making. The methodology used for the development of the thesis was through the different methods among them is the scientific in which it was possible to compile the information provided by the institution, with the inductive was obtained the economic and financial structure of the entity, in the same way was used the deductive method to identify the strengths and weaknesses presented by the cooperative, to make possible solutions, ie proposals for improvement based on the most relevant information about the research was necessary to use the synthetic method. Likewise, the methods mentioned above were complemented through different techniques such as direct observation, interview and bibliographic compilation. 5 In conclusion, it can be stated that Cooperative of Saving and Credit Huaquillas Ltda., until now a financial analysis has not been carried out, impeding in this way the adequate decision making, therefore, it does not have a maximum financial security which leads to a low capture of monetary resources, high arrears, unnecessary expenses and assets, this makes its income is minimized and the utility decreases, which is not satisfactory for the institution because its financial profitability does not allow it to grow in the financial market. Therefore, it is recommended to apply and develop a financial analysis in such a way that it will become an essential tool when making decisions in advance, increasing new products that allow reaching new goals and helping the growth of the institution, thus correctly using the resources it possesses and not exceeding its expenses to obtain an appreciable profit.